2020
DOI: 10.1021/acsnano.0c01180
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall, Ultracompact and Ultrahigh Efficient InGaN Micro Light Emitting Diodes (μLEDs) with Narrow Spectral Line Width

Abstract: Augmented reality and visual reality (AR and VR) microdisplays require micro light emitting diodes (μLEDs) with an ultrasmall dimension (≤5 μm), high external quantum efficiency (EQE), and narrow spectral line width. Unfortunately, dry etching which is the most crucial step for the fabrication of μLEDs in current approaches introduces severe damages, which seem to become an insurmountable challenge for achieving ultrasmall μLEDs with high EQE. Furthermore, it is well-known that μLEDs which require InGaN layers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 35 publications
0
53
0
Order By: Relevance
“…76,77) Also, a bottom-up selective growth method to form μLED mesas was able to avoid the generation of non-radiative recombination centers on the sidewalls. 78) As a result, InGaN blue μLEDs are demonstrated to have remarkable performance even when the device dimension decreases to 10 μm or less. 79,80) However, extending the emission wavelength to the red region to realize InGaN red μLEDs is still challenging.…”
Section: Ingan Red μLedsmentioning
confidence: 99%
“…76,77) Also, a bottom-up selective growth method to form μLED mesas was able to avoid the generation of non-radiative recombination centers on the sidewalls. 78) As a result, InGaN blue μLEDs are demonstrated to have remarkable performance even when the device dimension decreases to 10 μm or less. 79,80) However, extending the emission wavelength to the red region to realize InGaN red μLEDs is still challenging.…”
Section: Ingan Red μLedsmentioning
confidence: 99%
“…This method can easily integrate RGB colors into matrices on the same substrate [7], yet the colorconversion efficiency of hybrid devices must be improved [8]. Another approach chooses to fabricate red and green µLEDs using different materials, AlInGaP for red µLEDs [9] and InGaN for green µLEDs [10]. This material difference causes a mismatched angular distribution between the red and green µLEDs [11], leading to a noticeable color shift at different observed angles.…”
mentioning
confidence: 99%
“…reliability, many studies have reported that the external quantum efficiency (EQE) of InGaN µLEDs decreases with chip size [3][4][5]. This size dependence of the EQE was caused by the non-radiative recombination at the edge of the device active region [6][7][8], which could be eliminated or avoided by using a combination of chemical treatment and atomic-layer deposition sidewall passivation [9] or the bottom-up growth method to form µLED mesas [10].…”
mentioning
confidence: 99%